(untitled) (Docentes 2.0 Journal, 2025)
University teaching has been conceptualized as an interactive process that goes beyond the transmission of knowledge, where priority is given to the teacher’s ability to foster critical thinking, the interpretation of concepts, and the integral development of students. The study aimed to analyze scientific productivity in the field of university teaching. It also identified prolific authors and their contributions to the development of the field. A research study was carried out within the positivist paradigm, using a systematic method with a quantitative approach, using a bibliographic documentary and cross-sectional approach. Six key aspects are analyzed: (1) Relevant authors; (2) Authors’ countries; (3) Geographic distribution; (4) Cited countries; (5) The temporal evolution of scientific production; and (6) Thematic analysis of publications in this field. The methodology used was a bibliometric analysis with visualization tools to identify publication patterns and international collaboration. The results reflect that Alcarria et al. (2018) is the most prolific author on the subject with four publications; Spain is the leading country in production in this field; Both Australia and Nigeria show a high level of scientific production; Portugal and Australia are the countries with the highest number of citations in this field; publications on university teaching have been increasing since 2015, among other results. The conclusion is that there has been significant growth in research on university teaching, with global expansion, but also limitations in international collaboration and the inclusion of emerging topics.